2022
DOI: 10.1186/s12887-022-03251-z
|View full text |Cite
|
Sign up to set email alerts
|

X-linked hyper IgM syndrome with severe eosinophilia: a case report and review of the literature

Abstract: Background Hyper IgM syndromes (HIGMS) are a group of rare primary immunodeficiency disorders. There are limited reports about HIGMS combined with severe eosinophilia. Case presentation In this report, we described a 2-year-old boy with chronic cough and symptoms of hypoxia. Lung computed tomography (CT) scan showed that diffuse ground-glass changes and eosinophils in peripheral blood increased significantly. Subsequent tests revealed a notable dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Hence, patients classically have high IgM but low serum levels of IgG and IgA, leading to an increased risk for bacterial infections. Since the CD40/CD40L pathway also mediates co-stimulation between activated CD4 + T cells and CD40-expressing monocytes, macrophages, and dendritic cells, mutations in either CD40L (X-linked) or in CD40 (AR) also lead to opportunistic infections, notably Pjp [ 257 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 ]. Similarly, nuclear factor-kappa-B essential modulator ( NEMO/IKKγ ) [ 311 , 312 , 313 ], inhibitor of kappa light chain gene enhancer in B cells, alpha ( IκBα ) [ 314 ], or nuclear factor kappa-B subunit 1 ( NFKB1 ) [ 315 , 316 ] are involved in CD40/CD40L signaling, and, when mutated, interfere with CD4 + T cell/APC co-stimulation, resulting in HIGM syndrome, for which there are reports of Pjp.…”
Section: Pneumocystismentioning
confidence: 99%
“…Hence, patients classically have high IgM but low serum levels of IgG and IgA, leading to an increased risk for bacterial infections. Since the CD40/CD40L pathway also mediates co-stimulation between activated CD4 + T cells and CD40-expressing monocytes, macrophages, and dendritic cells, mutations in either CD40L (X-linked) or in CD40 (AR) also lead to opportunistic infections, notably Pjp [ 257 , 298 , 299 , 300 , 301 , 302 , 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 ]. Similarly, nuclear factor-kappa-B essential modulator ( NEMO/IKKγ ) [ 311 , 312 , 313 ], inhibitor of kappa light chain gene enhancer in B cells, alpha ( IκBα ) [ 314 ], or nuclear factor kappa-B subunit 1 ( NFKB1 ) [ 315 , 316 ] are involved in CD40/CD40L signaling, and, when mutated, interfere with CD4 + T cell/APC co-stimulation, resulting in HIGM syndrome, for which there are reports of Pjp.…”
Section: Pneumocystismentioning
confidence: 99%
“…Li et al reported a case with XHIGM who also had severe eosinophilia and fungal infection. After receiving anti-fungal treatment and IVIg replacement, the patient underwent allogeneic stem cell transplantation, eventually being discharged in good condition [ 28 ]. Another study by Fan et al showed that children with XHIGM were more vulnerable to respiratory infections, including T. marneffei , which in turn would help pediatricians to identify XHIGM [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…146 The primary line of treatment involves immunoglobulin replacement therapy and prophylactic antibiotics to ward off infections. 147 Despite treatment, the average life expectancy after diagnosis is only 25 years. 148 Allo-HSCT may be considered in extreme cases, although some studies have shown that median survival time is similar for patients past the age of 10 treated with or without allo-HSCT, likely due to prior organ damage.…”
Section: Therapeutic Strategies For X-linked Hyper Igm Syndrome (Xhigm)mentioning
confidence: 99%
“…Despite its rarity, more than 130 pathogenic variants of CD40LG have been reported 146 . The primary line of treatment involves immunoglobulin replacement therapy and prophylactic antibiotics to ward off infections 147 . Despite treatment, the average life expectancy after diagnosis is only 25 years 148 .…”
Section: Precision In Practice: Highlighting Gene Therapy Innovations...mentioning
confidence: 99%